2019
DOI: 10.1111/1911-3846.12517
|View full text |Cite
|
Sign up to set email alerts
|

Does Audit Committee Accounting Expertise Help to Promote Audit Quality? Evidence from Auditor Reporting of Internal Control Weaknesses

Abstract: In this study, we examine whether audit committee accounting expertise helps to promote audit quality by motivating auditors to conduct diligent internal control audits and make appropriate internal control assessments because audit committee accounting expertise safeguards auditors from dismissal following adverse internal control opinions. Among clients with existing and likely internal control material weaknesses (as proxied by future restatements of audited financial statements), we find a greater likeliho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 81 publications
(177 reference statements)
5
62
1
1
Order By: Relevance
“…They explained their results by arguing that ex‐auditors may improve the monitoring role of the audit committee. Similarly, Lisic, Myers, Seidel, and Zhou (in press) found that the accounting experience of audit committee members improves audit quality by encouraging auditors to better assess internal control. The audit committees with the most accounting experience increased the chances that an auditor would report an adverse internal control audit opinion.…”
Section: Prior Research and Research Questionsmentioning
confidence: 95%
“…They explained their results by arguing that ex‐auditors may improve the monitoring role of the audit committee. Similarly, Lisic, Myers, Seidel, and Zhou (in press) found that the accounting experience of audit committee members improves audit quality by encouraging auditors to better assess internal control. The audit committees with the most accounting experience increased the chances that an auditor would report an adverse internal control audit opinion.…”
Section: Prior Research and Research Questionsmentioning
confidence: 95%
“…On the one hand, some researchers study the effectiveness of the audit committee in light of the growing concern that the main reason for the existence of such committees is symbolic compliance with regulations, rather than fundamental oversight of the financial operations. Lisic et al (2019), Lisic et al (2016), and Bruynseels and Cardinaels (2014), for example, suggest that the expertise of audit committees does not automatically make the quality of the reporting process more reliable, that is, it does not mean that there will be fewer cases with reported material weaknesses. In addition to that, Lisic et al (2016) criticize the way boards and their subcommittees (such as the audit committee), are organized in the United States.…”
Section: Who Are the Actors?mentioning
confidence: 99%
“…Furthermore, independent directors need to protect their reputation by improving the level of monitoring, thus leading to better financial performance. Empirical evidence in Abbott et al (2003) and Lisic et al (2019) refers to audit committee effectiveness by assuming that audit committee independence and expertise has a positive association with audit fees. Given the significant value of the relationship between politics and business, it is important to examine how audit fees are influenced by audit committee characteristics.…”
Section: The Role Of Audit Committees In Maintaining Audit Quality Thmentioning
confidence: 99%
“…Over the past decade, the role of audit committees has become increasingly significant as high profile corporate scandals, such as Enron and WorldCom, have caused chaotic problems for the credibility of corporate governance. The need for more audit committees has been given attention through the combination of legislation and support through best practice guidelines, while in the post-Sarbanes Oxley Act (SOX) era, the key responsibilities of audit committees have the potential to influence operations, strategy and firm performance (Karim et al 2015 andLisic et al 2019). The issues concerning audit committees and corporate governance have been highlighted in many prior studies to improve financial reporting and audit quality (Neal et al 2009;Cohen et al 2004;Krishnan and Visvanathan 2007;Peasnell et al 2000;Turley and Zaman 2007;Jamil and Nelson, 2011;De Vlaminck and Sarens 2015;Lisic, 2019, Muslih, 2020.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation